Highly Hydrophobic Conductive Polyester Fabric Based on Homogeneous Coating Surface Treatment. Issue 3 (11th February 2019) - Zhou, Cun; Li, Yeran; Jin, Xin; He, Yaxi; Xiao, Changfa; Wang, Wenyu
ABSTRACT: A highly hydrophobic conductive polyester (PET-HE) fabric was prepared by a simple two-steps method. Firstly, homogeneous coating (the mixture of PET and carbon black (CB)) was uniformly coated on the PET fabric, which through curing in water coagulation bath and electrically conductive (PET-E) fabric was prepared. Then the solvent-induced crystallization process was adopted to PET-E fabric to endow the hydrophobic property. Investigations showed that PET-HE treated fabrics exhibited better hydrophobic and conductivity when the content of PET is 9wt% and the content of CB is the range of 8wt%-10wt%. The prepared polyester fabric proved to have such features as WCA was about 145°and surface resistance was about 300 Ω.GRAPHICAL ABSTRACT Graphical Abstract: